Acopladores de cristais fotônicos e acesso múltiplo por divisão de código óptico (OCDMA) com pulsos ultracurtos em fibras de Bragg - Lopes, Marcus Vinícius Pinheiro (2012)
This paper presents numerical simulation studies of propagation/switching of ultra-short pulses in photonic crystal couplers and Optical Code Division Multiple Access (OCDMA) using Fiber Bragg Grating (FBG). For coding were obtained analytically Gold codes. In the analysis of photonic crystal couplers (microstructured) investigated the properties of the propagation of light pulses as Sólitons. Ultra-short pulses of minimum duration of 100 femtoseconds (fs) were used. For this type of propagation in couplers, must be solved numerically the Equation nonlinear Schrödinger Generalized (ENLSG) of the coupled modes in accordance with the addition of third order dispersion, intrapulse Raman scattering, self-steepening and the dispersion of coupling coefficient. A coupler with coupling length of 1.8 cm and length 33 cm was simulated. Using this device length, the high-order effects (dispersion, self-steepening, raman, dispersion of the coupling) were important factors to consider. But, for small devices, with up to two coupling lengths, these effects may be ignored. In the second analysis, we studied the coding range of 5 Gold codes using an FBG encoder/decoder of length 41.58 mm. For the grid used, the encoding amplitude and interference between users of this device have been investigated. There was an increase of interference by adding values of users starting from 6 dB to about 10.5 dB for this device. Using photonic couplers with the FBG linear switching pulses between the channels of the coupler could be visualized to high gains (from 50 decibels).